Research on Influence of Pile-arch Conversion Structure on Existing Tunnel. Issue 1 (January 2020) - Deng, Zhiheng; Gao, Xiliang; Yang, Menggen; Yan, Feiyue; Qi, Xingxin; Qiu, Wenge
Abstract: Based on the actual project of Chongqing North Station project, this paper uses the software Flac3D to construct the excavation conditions of the foundation pit near the tunnel. A pile-arch conversion structure was applied above the tunnel. By examining the stress and axial force of the tunnel and calculating its safety factor, the advantages of the arch structure over the flat beam were explained, providing guidance and reference for similar projects in the future.